The Disaster Situation of Van Province and Site Selection Practices in Disaster Housing - Cafer GİYİK; Reşat Atalay OYGUÇ; Serhat Anıktar (Doğal Afetler ve Çevre Dergisi)
Depending on the geological structure of the land, its geographical location and meteorological conditions, Van Province is exposed to disasters such as earthquakes, landslides, floods, floods, rockfalls, avalanches and rising water levels of Lake Van. Although Van carries different disaster risks in terms of disaster, the most earthquake damage occurs in the city due to the tectonic structures that produce earthquakes in the region. The main reason why structures are damaged in disasters is the selection of places in areas with disaster risk and the construction of structures that are not resistant to disasters without disaster risk analysis. In the disasters experienced between 2000 and 2020 in Van, 144.230 buildings were damaged in different degrees and loss of life occurred. In this process, a total of 29,788 houses were built with different financing models and construction methods to meet the shelter needs of the disaster victims and return their lives to normal. Experienced disasters show that disaster damages cannot be prevented without a solid and suitable structure on the right ground. Different factors such as disaster, geological, geomorphological structure, socioeconomic structures of the victims and legal regulations are effective in site selection. The parcel sizes of the place to be selected should be suitable for the regional conditions, geographical structure, family and household sizes, social, cultural habits, and business sectors of the disaster victims. Since the workplace-housing relationship of the disaster survivors who have been relocated within the scope of internal resettlement is a problem after the disaster, this issue should be considered in site selection. In the study, the disaster management of Van Province and the location selection practices of disaster houses built in Van by disaster management units within the scope of post-disaster recovery activities were examined.